Is landscape-scale wild dog control the best practice?. Issue 1 (2nd January 2017) - Allen, Lee
ABSTRACT: Landscape-scale lethal control, achieved through better coordination of, and greater participation in, lethal control programs is promoted as the best-practice solution to Australia's wild dog problem. Three issues obstruct attempts to manage wild dogs at this scale. Firstly, wild dogs are framed as serious predators of livestock in general when many beef producers and non-livestock enterprises are unaffected or only sometimes affected by wild dogs. The involvement of all landholders in wild dog control is considered crucial to its success at a landscape scale. Secondly, short-lived and variable efficacy and immigration including from long-distance dispersal frustrate attempts to suppress and maintain wild dogs at low densities at the landscape scale. Finally, wild dogs can have positive, neutral or benign impacts for stakeholders. This makes participation in landscape-scale lethal control programs very difficult to achieve. Framed as serious predators of sheep and goats and only sometimes of calves of beef cattle, best-practice wild dog control should focus on strategies that prevent the ingress of dogs onto those properties troubled by predation. Managers who do not directly suffer predation losses or who derive a benefit from them preying on other pests should weigh up whether they undertake lethal control.